'It gives you the skills of how you can cope': Exploring the self‐reported experience of patients receiving in‐centre haemodialysis on participating in chosen art activities - Francesca Taylor; Vari M. Drennan; Marie‐Louise Turner; Jeunita Jones; Joyce Popoola (Wiley, 2021)
Abstract Background Increasing numbers of patients are receiving dialysis, particularly in high‐income countries. Patients receiving haemodialysis often experience fatigue, anxiety, depression and boredom. It is suggested that arts activities could have a therapeutic effect. Objective This study aimed to explore patients' perspectives of participating while on dialysis in chosen arts and creative living activities provided by tutors at the bedside. Design Qualitative semi‐structured interviews in the interpretive tradition were conducted, with thematic analysis. Setting and Participants Fifteen patients of different ages, genders and ethnicities who participated in an arts activity while receiving haemodialysis in an inner‐city dialysis unit in England were included in this study. Results Participants reported positive experiences of engaging in art activities. Their views on the value of the activities were grouped into five themes: diversion from receiving haemodialysis, a sense of achievement, contribution to a more positive self‐identity, increased confidence and motivation and a therapeutic talking relationship. Participants suggested that patient peer promotion of the activities could increase uptake, with patient choice of activity seen as important. Conclusions Participation in a chosen arts activity while receiving haemodialysis was perceived by patients to have positive psychosocial effects. We theorize three potential explanatory mechanisms for these effects: That the experience of participating in the activities engendered positive psychological states of 'being in the flow'; enhanced self‐esteem to add to personal coping mechanisms; and offered additional facets to the patient's identity that countered the stigmatizing effect of receiving dialysis. Patient or Public Contribution Patients and public representatives advised on the design, research methods and tools.